The Effect of Solar Panel Tilt Angle Automation on the Efficiency of Hybrid Renewable Energy Systems (HRES) - Diraharja, Rifat Satrio; Rhakasywi, Damora; Fahrudin, Fahrudin (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): Renewable energy is increasingly critical as fossil fuel reserves decline and global energy demand rises. Background (Specific): Hybrid Renewable Energy Systems (HRES) that combine solar photovoltaic (PV) and wind energy offer reliable alternatives, but fixed solar panels limit energy capture due to suboptimal orientation. Knowledge Gap: While solar tracking has been explored, its effectiveness within small-scale HRES prototypes in real-world conditions remains underexamined. Aim: This study investigates the impact of automated solar panel tilt adjustment on the efficiency of a small-scale HRES integrating a vertical-axis wind turbine. Results: Experimental testing over five days demonstrated that the automated tilt system enhanced solar energy capture by 23–43% compared to fixed-tilt configurations, with daily energy outputs reaching 1,020 Wh, although battery charging remained capped at 60% due to charge controller restrictions. Novelty: The research highlights a low-cost, single-axis automation mechanism controlled by ESP32 and LDR sensors, providing a feasible and scalable solution for off-grid applications. Implications: Findings underscore the potential of affordable solar tracking in hybrid systems to improve energy access in rural or remote areas, while emphasizing the need for improved storage management to fully realize efficiency gains Highlights: Automated tilt improved solar energy capture by 23–43%. Low-cost, ESP32–LDR system proved feasible for rural use. Battery charging limited at 60% due to controller settings. Keywords: Solar Tracking, Hybrid Renewable Energy, Tilt Angle Automation, Energy Efficiency, Off-Grid Systems